Improving PV Hosting Capacity by Implementing Energy Storage Systems on Distribution Networks - Giacomini, Jairo [UNESP]; Cebrian, Juan Carlos [UNESP]; Morales Paredes, Helmo Kelis [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
High penetration rates of distributed generation using photovoltaic systems (PVS) bring challenges for distribution network operation, mainly due to PVS presenting intermittent generation characteristics. Strategies such as controlling the active and reactive power supplied to the network by inverter connected to the PVS are adopted to overcome the challenges. The use of electric battery storage systems (EBSS) has proved to be a viable alternative to increase the host capacity of distribution networks. An EBSS charging strategy during the solar generation period and discharging during the period of highest demand can contribute to reducing consumers' energy costs and network loading. This paper investigates the PVS hosting capacity variation in distribution networks, without EBSS and by a methodology for allocating EBSS on the network busbars. The results show that the most expressive increase in PVS hosting capacity is obtained in busbars with higher power loads and when the periods of highest demand are displaced from the period of photovoltaic generation.
Keywords: distribution networks; energy storage; hosting capacity; photovoltaic generation system